Program Edukasi Pasien dan Keluarga terhadap Kepuasan Pasien - Nurhafizah Nurhafizah; Siti Saidah Nasution; Mahnum Lailan Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify how patient and family education programs affect patient satisfaction. This research method is quantitative with a quasi-experimental design using a one-group pretest-posttest approach. The results showed a significant effect between the educational program and patient satisfaction with a value of p = 0.000 (pâ‰¤0.05), where the coefficient of determination showed the magnitude of the effect of the education program on patient satisfaction with an R-value of squared = 0.133. In conclusion, there is a significant effect between educational programs on patient satisfaction on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles with the most dominant influence on the dimensions of reliability. Keywords: Patient Satisfaction, Patient and Family Education Program